CHARACTERISTICS OF HYPERTENSION IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS - Danti, Ida Ayu Mahari; Masyeni, Sri; Dewi, Saraswati Laksmi; Lestarini, Asri (JURNAL WIDYA MEDIKA, 2026)
Hypertension in Chronic Kidney Disease (CKD) remains a global health issue, often presenting as resistant hypertension even with multiple antihypertensive medications. This study aims to describe the characteristics of hypertension in CKD patients undergoing hemodialysis at Sanjiwani Regional Hospital. A descriptive observational study with a cross-sectional design was conducted using secondary data from medical records of CKD patients with hypertension who underwent hemodialysis from January 2022 to December 2023, involving 100 patients. The study found that the highest proportion of hypertensive CKD patients were aged 46-65 years (60%), predominantly male (63%), with grade 1 hypertension (69%). The majority had CKD for ≥5 years (60%) and were taking ≤3 antihypertensive medications (72%). The commonly used antihypertensive drug class was calcium channel blockers (68%), with diabetes mellitus identified as the primary etiology (45%). Many CKD patients experience resistant hypertension, primarily affecting males aged 46-65 years.